RHYME, RHYTHM, AND RELIGIOUS VALUES IN THE QASIDAH ILA ARAFATI IN THE DIWAN OF AHMAD SYAUQI - Syauqy Mujahid Fathurrohman; Rohanda Rohanda; Yadi Mardiansyah (ALLAIS Journal of Arabic Language and Literature, 2026)
This study aims to determine the changes in rhyme, rhythm, and religious values in the qasidah Ila Arafati from the Diwan Ahmad Syauqi. This study uses a descriptive analytical method with qualitative research and an approach to the study of arudh and qawafi. The research data consists of 20 selected verses, out of a total of 41 verses in the qasidah Ila Arafati. Data collection techniques were carried out using observation and note taking methods, while data analysis techniques were conducted using taqthi arudhi to identify wazan, changes in zihaf and ilat, qafiyah analysis, and interpretation of meaning to reveal religious values. The results show that the qasidah uses Bahr Thawil with zihaf qabdh in hasywu and ilat hadzf in dharab. In terms of qafiyah, this qasidah uses the letter ta (ت) as its rawi muthlaq, classifying it as a taiyyah qasidah that is free from uyub qafiyah. In addition, this qasidah contains religious values, including the value of faith, worship (sharia) and morality. This study contributes to expanding Arabic literary studies through the analysis of arudh, qawafi, and religious values in Ahmad Syauqi’s qasidah Ila Arafati, which has received limited attention in previous research.